2006
DOI: 10.1109/memb.2006.1705746
|View full text |Cite
|
Sign up to set email alerts
|

Passing data and supplying power to neural implants

Abstract: The ischemia-induced death of cardiomyocytes results in scar formation and reduced contractility of the ventricle. Several preclinical and clinical studies have supported the notion that cell therapy may be used for cardiac regeneration. Most attempts for cardiomyoplasty have considered the bone marrow as the source of the "repair stem cell(s)," assuming that the hematopoietic stem cell can do the work. However, bone marrow is also the residence of other progenitor cells, including mesenchymal stem cells (MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…For instance, based on the known effects of infused MSCs on heart diseases (Schuster et al, 2004; Itescu et al, 2003; Minguell and Erices, 2006), it may be possible to develop an alternative therapeutic paradigm for use in third world countries or in situations in which adequate life-support is not readily available for patients suffering an acute myocardial infarct. Following this new approach, patients would be treated in a clinical facility that had frozen stores of bags of allogeneic MSCs available for infusion.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…For instance, based on the known effects of infused MSCs on heart diseases (Schuster et al, 2004; Itescu et al, 2003; Minguell and Erices, 2006), it may be possible to develop an alternative therapeutic paradigm for use in third world countries or in situations in which adequate life-support is not readily available for patients suffering an acute myocardial infarct. Following this new approach, patients would be treated in a clinical facility that had frozen stores of bags of allogeneic MSCs available for infusion.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Fuel cells based on enzymatic catalysts have also been shown to operate under physiological conditions but still require much improvement to become viable [54,55]. Interest has also been expressed in using human white blood cells as a source of electrons for an anode [56]. Experiments using white blood cells in phosphate-buffered saline solution with a ferric-cyanide cathode produced a low current level of 1-3 µAcm −2 but it could not determine if electron transport to the anode was through a direct or indirect process [57].…”
Section: Potential Applications For Microbial Fuel Cellsmentioning
confidence: 99%
“…MSC transplantation has been used in clinical trials and animal models to treat musculoskeletal injuries, improve cardiac function in cardiovascular disease and ameliorate the severity of graft-versus-host-disease [1]. In recent years, MSC transplantations have demonstrated therapeutic efficacy in treating different diseases but the underlying mechanism has been controversial [2-9]. Some reports have suggested that factors secreted by MSCs were responsible for the therapeutic effect on arteriogenesis, stem cell crypt in the intestine, ischemic injury, and hematopoiesis [9-20].…”
Section: Introductionmentioning
confidence: 99%